British American Tobacco’s partnership with Earthwatch Europe and its implications for public health - McDaniel, Patricia A. (2011)
This paper explores a partnership between British American Tobacco (BAT) and the environmental organisation Earthwatch Europe (EE) and considers its implications for countries implementing Article 5.3 of the World Health Organisation Framework Convention on Tobacco Control. We reviewed approximately 100 internal BAT documents, interviewed EE’s former executive director, and examined media accounts and BAT and EE websites. We analysed materials by reviewing them iteratively, identifying themes, constructing a timeline of events, and assembling a case study. BAT sought a partnership with EE to gain a global ally that could provide entrée into the larger NGO community. EE debated the ethics of working with BAT, resolving them in BAT’s favour and taking a narrow view of its own overall organizational mission. To protect its reputation, EE delayed public disclosure of the partnership. Instead, EE promoted it to policymakers and other NGOs, extending BAT’s reputation and reach into influential circles. The potential for normalising the tobacco industry presence within government through NGO partnerships, and the benefits that accrued to BAT even when the partnership was not being publicised, show why governments seeking to protect effective tobacco control policies from industry influence need to consider ways to identify and discourage “hidden” NGO partnerships.